1956
DOI: 10.1002/ajpa.1330140214
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric estimation of the pigment concentration in hair of various color grades

Abstract: ONE FIQWEHair color has long been considered a most useful criterion for distinguishing divisions of mankind and it has been recorded in many studies in physical anthropology. In most of these studies the colors have been determined subjectively, and have been assigned either names or grades determined by comparison of the hair with color charts, color wheels or standard colored hair samples. Although hair color is determined primarily by the amount and type of pigment present in the hair, there are many struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1961
1961
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Investigations into hair color have progressed from subjective visual ratings to spectrophotometric measures and biochemical quantifications. The first studies categorized hair color by visual inspection (Davenport and Davenport, 1909), an approach standardized in the Fischer-Saller Haarfarbentafel scale using 30 swatches (Hanna, 1956). Interested in using spectrophotometry, Harrison and Owen (1964) showed that the wavelength with the greatest power to distinguish between different quantities of dermal melanin is approximately 650 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into hair color have progressed from subjective visual ratings to spectrophotometric measures and biochemical quantifications. The first studies categorized hair color by visual inspection (Davenport and Davenport, 1909), an approach standardized in the Fischer-Saller Haarfarbentafel scale using 30 swatches (Hanna, 1956). Interested in using spectrophotometry, Harrison and Owen (1964) showed that the wavelength with the greatest power to distinguish between different quantities of dermal melanin is approximately 650 nm.…”
Section: Introductionmentioning
confidence: 99%